Spinal anaesthesia in elderly for laparoscopic cholecystectomy - Gautam, Binod (Journal of Kathmandu Medical College, 2018)
Background: Prevalence of aging patients appearing for laparoscopic cholecystectomy to treat cholelithiasis is ever on the rise. Associated co-morbidities make the elderly prone to peri-operative complications during laparoscopic cholecystectomy performed under general anaesthesia.Objectives: This study aims to assess the safety and applicability of spinal anaesthesia for the elderly undergoing laparoscopic cholecystectomy.Methodology: In this cross-sectional study, fifty-four patients of age 65 years or more undergoing laparoscopic cholecystectomy were studied. Hyperbaric Bupivacaine 15 milligrams was used in spinal anaesthesia to obtain sensory block to fifth thoracic dermatome. Local anaesthetics were instilled intra-peritoneally before surgical dissection. Surgery was performed through three ports with carbon dioxide pneumoperitoneum at eight mmHg intra-abdominal pressure. Data included demography, co-morbidities, need for analgesics or general anaesthesia, operative and post-operative complications and hospital stay. Univariate analysis for peri-operative events and bivariate analysis for outcome and explanatory variables were done.Results: The mean age was 71.4 years with co-morbidity in 40 patients. Conversion to open cholecystectomy occurred in three patients necessitating general anaesthesia. Surgery was completed laparoscopically under spinal anaesthesia in remaining 51 patients. Increment in intra-abdominal pressure was required in five patients. Six patients needed analgesics for shoulder pain. Intra-operative hypotension and shivering occurred in 15 and four patients respectively. Post-operatively, urinary retention and nausea occurred in four and three patients respectively. Mean hospital stay was 3.2 days.Conclusion: There is no undue risk in spinal anaesthesia for conducting laparoscopic cholecystectomy in the elderly and it is efficient for uncomplicated cholelithiasis with minimal modifications in surgical technique.